Comparative Study between Subannular T- Tube and Repetitive Transtympanic T-Tube Technique - Mohamed Eldabaa (Al-Azhar University, Faculty of Medicine (Damietta), 2020)
Background: Otitis media [OM] is the second most common disease of childhood after upper respiratory tract infection. There was no consensus on the ideal treatment modality yet. Aim of the work: To compare the use of trans-tympanic T tube [TTTT] and subannular T tube [SATT] in recurrent otitis media, recurrent otitis media with effusion or tympanic membrane retraction. Patients and Methods: This is a prospective controlled study, which was conducted at Al-Azhar university hospital [Damietta]. It included 40 patients that were randomly divided into two groups A and B: Group A: include 20 patients who were submitted to trans-tympanic T-tube. Group B included 20 patients who were submitted to sub annular T-tube. Patient data and outcome were documented and compared. Results: The duration that TTTTs and SATTs remained in place ranged from 4 to 19 months with a mean of 10.62 and there was a significant decrease of duration in TTTT in comparison to SATT groups [7.28 vs 14.80 respectively]. Besides, in 14 cases in the SATT group, the tube is still in place. Extrusion was reported in 10 cases [8 in the TTTT group and 2 in the SATT group] and finally removal was reported in 6 patients [2 in TTTT group and 4 in the SATT group. Conclusion: The use of SATTs for long term middle ear ventilation is safe and more efficient than V-T Grommet TTTTs for maintaining middle ear ventilation and prevention of recurrent interventions in children with less otorrhea and plugged tubes.